The kynurenine pathway presents multi-faceted metabolic vulnerabilities in cancer - León-Letelier, Ricardo A.; Dou, Rongzhang; Vykoukal, Jody; Sater, Ali Hussein Abdel; Ostrin, Edwin; Hanash, Samir; Fahrmann, Johannes F. (Frontiers in Oncology, 2023)
The kynurenine pathway (KP) and associated catabolites play key roles in promoting tumor progression and modulating the host anti-tumor immune response. To date, considerable focus has been on the role of indoleamine 2,3-dioxygenase 1 (IDO1) and its catabolite, kynurenine (Kyn).However, increasing evidence has demonstrated that downstream KP enzymes and their associated metabolite products can also elicit tumor-microenvironment immune suppression. These advancements in our understanding of the tumor promotive role of the KP have led to the conception of novel therapeutic strategies to target the KP pathway for anti-cancer effects and reversal of immune escape. This review aims to 1) highlight the known biological functions of key enzymes in the KP, and 2) provide a comprehensive overview of existing and emerging therapies aimed at targeting discrete enzymes in the KP for anti-cancer treatment.